A composite ultra-high temperature quartz crucible and preparation method thereof

By dealing with high-pure quartz sand under alkaline conditions and introducing SI-C bonds, combined with high-purity silicon nitride and quartz fiber, solving the strength and corrosion resistance of traditional quartz crickets in high temperature environments, preparing a higher level is higher Temperature resistance, strength, and corrosion -resistant composite ultra -high -temperature quartz 坩埚.

CN119143516BActive Publication Date: 2025-01-28BAOTOU ZHUOYU TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411604743.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-01-28
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

Traditional quartz crucibles have problems such as insufficient strength, easy corrosion and poor temperature resistance in high temperature and complex process environments, which affect the crystal growth quality and production efficiency.

Method used

Under alkaline conditions, high-pure quartz sand obtains hydroxylson, and react with the silicol solution to form contracted quartz sand, adding the Si-O-SI key. Then add high-pure graphite and carbon powder to replace some oxygen atoms to form Si-C bonds to improve the temperature resistance and resistance of the 坩埚. At the same time, high -purity silicon nitride and quartz fiber are introduced to enhance the performance of heat shock resistance, and inner and outer layers are added to the inner and outer layers to add internal coating materials and outer base materials to improve corrosion resistance and overall strength.

Benefits of technology

The prepared composite ultra -high -temperature quartz cymbals have a significant improvement of temperature, strength, and corrosion resistance, and can work stably in a complex process environment to ensure the growth quality of the crystal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143516B_ABST
    Figure CN119143516B_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of crucible manufacturing, and specifically refers to a composite ultra-high temperature quartz crucible and a preparation method thereof. The raw materials for preparing the composite ultra-high temperature quartz crucible include 10-12 parts of a main mixture, 0.5 parts of an inner coating material, and 2-3 parts of an outer substrate material; high-purity quartz sand is treated under alkaline conditions to obtain hydroxylated quartz sand, which reacts with a silanol solution to obtain condensed quartz sand, and high-purity graphite powder and high-purity carbon powder are further added to partially replace oxygen in the condensed quartz sand to obtain composite quartz sand rich in Si-O-Si bonds and Si-C bonds, and high-purity silicon powder is used as a substrate, high-purity silicon nitride is introduced, and a main mixture is prepared to improve the overall temperature resistance and thermal shock resistance of the material; an inner coating material is arranged in an inner layer to prevent corrosion of the material; and an outer substrate material is arranged on the periphery to enhance the overall strength and toughness of the quartz crucible and resist corrosion of the quartz crucible by the external environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of crucible manufacturing, and specifically refers to a composite ultra-high temperature quartz crucible and a preparation method thereof. Background Art

[0002] With the continuous advancement of technology, the temperature of crystal growth continues to increase, which poses higher challenges to the temperature resistance, strength and corrosion resistance of quartz crucibles.

[0003] When faced with higher temperatures and more complex process environments, traditional quartz crucibles may have problems such as insufficient strength, susceptibility to corrosion, and poor temperature resistance, which may affect the growth quality and production efficiency of the crystal.

[0004] In order to solve the above problems, it is necessary to develop a new type of composite ultra-high temperature quartz crucible. This crucible should have higher strength, temperature resistance and corrosion resistance, be able to work stably under complex process environments, and also have good impurity removal capabilities to ensure the growth quality of crystals. Summary of the invention

[0005] In view of the defects of the prior art, the present invention discloses a composite ultra-high temperature quartz crucible and a preparation method thereof. High-purity quartz sand is treated under alkaline conditions to obtain hydroxylated quartz sand, which reacts with a silanol solution to obtain condensed quartz sand to form Si-O-Si bonds, and high-purity graphite powder and high-purity carbon powder are further added to partially replace the oxygen in the condensed quartz sand to obtain Si-C bonds, thereby improving the overall heat resistance and external force resistance of the quartz sand. High-purity silicon powder is then used as a substrate, and high-purity silicon nitride is introduced to prepare a composite main mixture to improve the overall thermal shock resistance of the material. An inner coating material is provided in the inner layer. High-purity silica sol, high-purity silicon carbide and high-purity barium silicate are selected as reaction materials, among which silica sol can improve the dispersibility very well. At the same time, under high temperature conditions, silica sol loses water, and high-purity barium silicate decomposes into barium oxide and silicon dioxide. Barium oxide reacts with water to obtain barium hydroxide, which can be used as an impurity scavenger to adsorb impurities in the crystal growth melt and improve corrosion resistance. At the same time, an external base material is arranged on the periphery to enhance the overall strength and toughness of the quartz crucible and resist the corrosion of the external environment to the quartz crucible. The prepared composite ultra-high temperature quartz crucible has high strength, temperature resistance and corrosion resistance.

[0006] To achieve the above object, the technical solution adopted by the present invention is a composite ultra-high temperature quartz crucible, characterized in that it is prepared from the following raw materials in parts by weight: 10-12 parts of the main mixture, 0.5 parts of the inner coating material, and 2-3 parts of the outer base material;

[0007] Furthermore, the preparation method of the binder comprises the following steps:

[0008] S1: Weigh water, polyethylene glycol, sodium polyacrylate and ethylene glycol in a mass ratio of 10:4-6:0.1-0.3:1-3;

[0009] S2: adding the polyethylene glycol weighed in step S1 into water, heating and stirring, the heating temperature is 60-80°C, the heating time is 30 minutes, to obtain a polyethylene glycol mixed aqueous solution, then adding sodium polyacrylate to the polyethylene glycol mixed aqueous solution, stirring at room temperature for 6-8 hours, to obtain a viscous mixture;

[0010] S3: Add ethylene glycol to the viscous mixture obtained in step S2 and perform ultrasound for 30 minutes. The mass ratio of the viscous mixture to ethylene glycol is 2:1-3, the ultrasound power is 0.5-0.8 kw, and the mixture is heated and stirred. The heating temperature is 65-75°C and the heating time is 2 hours to obtain a binder.

[0011] Furthermore, the preparation method of the condensed quartz sand comprises the following steps:

[0012] M1: Weigh high-purity quartz sand, silane coupling agent and sodium hydroxide solution in a mass ratio of 10-15:3-5:1.5;

[0013] M2: The sodium hydroxide solution weighed in step M1, the concentration of which is 1 mol / L, is added to a high-pressure reactor and diluted 5 times with water to obtain a diluted alkaline solution, the high-purity quartz sand weighed in step M1 is added to the diluted alkaline solution and stirred evenly to obtain a mixture solution I, which is then heated at a temperature of 120-180° C. for 4-6 hours, and naturally cooled to room temperature to obtain hydroxylated quartz sand;

[0014] M3: Add water to the hydroxylated quartz sand obtained in step M2 and filter until the filtrate is neutral to obtain pure hydroxylated quartz sand. Dry the obtained pure hydroxylated quartz sand at a temperature of 60° C. for 24 h, collect the powder, and obtain hydroxylated quartz sand powder;

[0015] M4: Stir and mix the silane coupling agent and water weighed in step M1, the mass ratio of the silane coupling agent to water is 3-5:15, add 3 mol / L hydrochloric acid, control the pH range to 3-5, and obtain a silane coupling agent acid solution, then heat and stir the silane coupling agent acid solution, the heating temperature is 70-90°C, the heating time is 2h, and a silanol solution is obtained;

[0016] M5: Add the hydroxylated quartz sand obtained in step M2 to the silanol solution obtained in step M4, the mass ratio of hydroxylated quartz sand to silanol solution is 1:2-4, heat and stir, the heating temperature is 60-80°C, the heating time is 6h, naturally cool to room temperature, centrifuge to remove the solution and dry to obtain condensed quartz sand.

[0017] Furthermore, the preparation method of the composite quartz sand comprises the following steps:

[0018] N1: Weigh condensed quartz sand, high-purity graphite powder and high-purity carbon powder in a mass ratio of 6-10:1.5-2.5:1;

[0019] N2: The condensed quartz sand, high-purity graphite powder and high-purity carbon powder weighed in step N1 are stirred and mixed evenly, and heated in an argon atmosphere at 20 L / min using a resistance furnace at a heating temperature of 1600-1800° C. for 6 hours, and then naturally cooled to room temperature to obtain composite quartz sand.

[0020] Furthermore, the preparation method of the main mixture comprises the following steps:

[0021] V1: Weigh composite quartz sand, high-purity silicon nitride, high-purity silicon powder, high-purity quartz fiber, polyethylene glycol, binder and ethanol in a mass ratio of 15-20:6-8:2:3-7:4.5-6.5:4-6:3-6;

[0022] V2: Evenly mix the composite quartz sand, high-purity silicon nitride and high-purity silicon powder weighed in step V1 to obtain mixed sand;

[0023] V3: Add the polyethylene glycol weighed in step V1 to ethanol and stir evenly to obtain a polyethylene glycol solution, then add the high-purity quartz fiber weighed in step V1 to the polyethylene glycol solution for ultrasonic treatment, with an ultrasonic power of 0.3-0.5 kW and an ultrasonic time of 20 min, and heat and stir to obtain a quartz fiber suspension at a heating temperature of 50-80°C and a heating time of 4 h;

[0024] V4: Slowly add the quartz fiber suspension obtained in step V3 to the mixed sand obtained in step V2, the mass ratio of the quartz fiber suspension to the mixed sand is 1.5-2.5:4, and slowly stir with a peristaltic pump at a stirring speed of 25 r / min for 2 h, and then dry at a drying temperature of 65°C for 12 h to obtain composite sand;

[0025] V5: Add the binder into the composite sand obtained in step V4 in the form of spraying, and stir. The mass ratio of the binder to the composite sand is 4-6:9. The stirring time is 3 hours. Then, dry the mixture at a drying temperature of 50-70°C and a drying time of 24 hours to obtain a main mixture.

[0026] Furthermore, the preparation method of the inner coating material comprises the following steps:

[0027] Y1: Weigh high-purity silica sol, high-purity silicon carbide and high-purity barium silicate in a mass ratio of 3:4-6:1.5-3.5;

[0028] Y2: The high-purity silica sol weighed in step Y1 is subjected to ultrasonic treatment at a power of 0.8-1.2 kW and a time of 30 min to obtain a uniform silica sol. The high-purity silicon carbide and high-purity barium silicate weighed in step Y1 are then added to the uniform silica sol and stirred at a speed of 800-1200 r / min for 2-4 h to obtain an inner coating material.

[0029] Furthermore, the method for preparing the outer base material comprises the following steps:

[0030] X1: Weigh high-purity alumina powder, high-purity silicon carbide powder, high-purity quartz fiber and epoxy resin glue in a mass ratio of 1.5-2:2-4:3:3-5;

[0031] X2: The high-purity aluminum oxide powder and the high-purity silicon carbide powder weighed in step X1 are fully mixed to obtain a mixture I;

[0032] X3: adding the high-purity quartz fiber weighed in step X1 to the epoxy resin glue, heating and stirring, the heating temperature is 50-70° C., the heating time is 60 min, the stirring speed is 300-500 r / min, and the stirring time is 1-3 h, to obtain a mixture II;

[0033] X4: Add the mixture I obtained in step X2 to the mixture II obtained in step X3 and stir evenly. The mass ratio of mixture I to mixture II is 2:0.5-1.5 to obtain the outer base material.

[0034] The present invention also provides a method for preparing a composite ultra-high temperature quartz crucible, comprising the following steps:

[0035] Step 1: Weigh 10-12 parts of the main mixture, 0.5 parts of the inner coating material, and 2-3 parts of the outer base material;

[0036] Step 2: slowly injecting the main mixture weighed in step 1 into a mold of a quartz crucible, and curing and molding it at a temperature of 300-500° C. and a pressure of 100 MPa using a hot isostatic press to obtain a quartz crucible body, and then slowly and evenly injecting the outer base material onto the outer surface of the quartz crucible body, and pressing at a temperature of 300-500° C. and a pressure of 200-400 MPa to obtain a quartz crucible blank;

[0037] Step 3: evenly spraying the inner coating material weighed in step 1 onto the inner surface of the quartz crucible blank obtained in step 2 to obtain a complete quartz crucible precursor;

[0038] Step 4: Place the quartz crucible precursor obtained in step 3 into a high temperature furnace, sinter it at 1500-2000°C in an argon atmosphere with an argon flow rate of 25 L / min for 8 hours, and cool it naturally to room temperature to obtain a composite ultra-high temperature quartz crucible.

[0039] The beneficial effects achieved by the present invention are as follows:

[0040] The composite ultra-high temperature quartz crucible prepared by the present invention first obtains hydroxylated quartz sand by treating high-purity quartz sand under alkaline conditions, and obtains condensed quartz sand rich in Si-O-Si bonds by reacting with a silanol solution for dehydration and condensation, and further obtains composite quartz sand containing Si-C bonds by adding high-purity graphite powder and high-purity carbon powder to replace part of oxygen, thereby improving the overall heat resistance and thermal shock resistance of the quartz crucible, and then using high-purity silicon powder as a base material, introducing high-purity silicon nitride and high-purity quartz fiber into the composite quartz sand, further enhancing the heat resistance and mechanical strength of the quartz crucible, and adding a binder to improve the bonding force between molecules, so that the molecules of the prepared main mixture are more compact, and bubbles are avoided in the preparation process to damage the quartz crucible.

[0041] The composite ultra-high temperature quartz crucible prepared by the present invention uses high-purity silica sol, high-purity silicon carbide and high-purity barium silicate as reaction materials for the first time to prepare an inner coating material, wherein the silica sol can improve the dispersibility very well, can adhere well to the surface of the main mixture, and improve the adhesion between the materials. At the same time, under high temperature conditions, the silica sol loses water, and the high-purity barium silicate is decomposed into barium oxide and silicon dioxide, wherein the barium oxide reacts with water to obtain barium hydroxide, which can be used as an impurity scavenger to adsorb impurities in the crystal growth melt. As an inner coating, it can better prevent the main mixture from being corroded, and make the prepared composite ultra-high temperature quartz crucible have stronger heat resistance and corrosion resistance.

[0042] The composite ultra-high temperature quartz crucible prepared by the present invention uses high-purity alumina powder, high-purity silicon carbide powder, high-purity quartz fiber and epoxy resin glue as raw materials for the first time to prepare the outer base material of the quartz crucible, thereby improving the overall heat resistance, mechanical and corrosion resistance of the composite ultra-high temperature quartz crucible, and selecting epoxy resin glue as the adhesive material to improve the adsorption strength of the prepared outer base material and the main mixture.

[0043] The composite ultra-high temperature quartz crucible prepared by the present invention selects different materials as raw materials for preparing the outer layer, the body and the inner layer respectively during the preparation process, so as to prepare a composite high temperature resistant quartz crucible with higher strength than that of the prior art. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 A diagram showing a preparation method according to an embodiment of the present invention;

[0045] Figure 2 Material distribution diagram of the composite high-temperature resistant quartz crucible prepared in an embodiment of the present invention.

[0046] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION

[0047] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0048] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.

[0049] The preparation methods and material distribution in the following examples are referred to Figure 1 and Figure 2 Unless otherwise specified, all methods are conventional; the materials used in the following embodiments, unless otherwise specified, are new materials purchased from the market.

[0050] Example 1: A composite ultra-high temperature quartz crucible, characterized in that it is prepared from the following raw materials in parts by weight: 10 parts of a main mixture, 0.5 parts of an inner coating material, and 2 parts of an outer base material;

[0051] The preparation method of the binder comprises the following steps:

[0052] S1: Weigh water, polyethylene glycol, sodium polyacrylate and ethylene glycol in a mass ratio of 10:4:0.1:1;

[0053] S2: adding the polyethylene glycol weighed in step S1 into water, heating the temperature to 60°C and stirring for 30 minutes to obtain a polyethylene glycol mixed aqueous solution, then adding sodium polyacrylate to the polyethylene glycol mixed aqueous solution, stirring at room temperature for 6 hours to obtain a viscous mixture;

[0054] S3: Add ethylene glycol to the viscous mixture obtained in step S2 for ultrasonic treatment. The mass ratio of the viscous mixture to ethylene glycol is 2:1. The ultrasonic time is 30 minutes and the ultrasonic power is 0.5 kW. Heat the temperature to 65°C and stir for 2 hours to obtain a binder.

[0055] The preparation method of the condensed quartz sand comprises the following steps:

[0056] M1: Weigh high-purity quartz sand, silane coupling agent and sodium hydroxide solution in a mass ratio of 10:3:1.5;

[0057] M2: The sodium hydroxide solution weighed in step M1, the concentration of which is 1 mol / L, is added to a high-pressure reactor and diluted 5 times with water to obtain a diluted alkaline solution, the high-purity quartz sand weighed in step M1 is added to the diluted alkaline solution and stirred evenly to obtain a mixture solution I, which is then heated to 120° C. for 4 hours and naturally cooled to room temperature to obtain hydroxylated quartz sand;

[0058] M3: Add water to the hydroxylated quartz sand obtained in step M2 and filter until the filtrate is neutral to obtain pure hydroxylated quartz sand. Dry the obtained pure hydroxylated quartz sand at a temperature of 60° C. for 24 h, collect the powder, and obtain hydroxylated quartz sand powder;

[0059] M4: Stir and mix the silane coupling agent and water weighed in step M1, the mass ratio of the silane coupling agent to water is 3:15, add 3 mol / L hydrochloric acid, adjust the pH to 3, and obtain a silane coupling agent acid solution, then heat the silane coupling agent acid solution to 70° C. and stir for 2 h to obtain a silanol solution;

[0060] M5: Add the hydroxylated quartz sand obtained in step M2 to the silanol solution obtained in step M4, the mass ratio of hydroxylated quartz sand to silanol solution is 1:2, heat to 60°C and stir for 6 hours, naturally cool to room temperature, centrifuge to remove the solution and dry to obtain condensed quartz sand.

[0061] The preparation method of the composite quartz sand comprises the following steps:

[0062] N1: Weigh condensed quartz sand, high-purity graphite powder and high-purity carbon powder in a mass ratio of 6:1.5:1;

[0063] N2: The condensed quartz sand, high-purity graphite powder and high-purity carbon powder weighed in step N1 are stirred and mixed evenly, and heated to 1600° C. for 6 hours in an argon gas flow rate of 20 L / min using a resistance furnace, and then naturally cooled to room temperature to obtain composite quartz sand.

[0064] The preparation method of the main mixture comprises the following steps:

[0065] V1: Weigh composite quartz sand, high-purity silicon nitride, high-purity silicon powder, high-purity quartz fiber, polyethylene glycol, binder and ethanol in a mass ratio of 15:6:2:3:4.5:4:3;

[0066] V2: Evenly mix the composite quartz sand, high-purity silicon nitride and high-purity silicon powder weighed in step V1 to obtain mixed sand;

[0067] V3: Add the polyethylene glycol weighed in step V1 into ethanol and stir evenly to obtain a polyethylene glycol solution, then add the high-purity quartz fiber weighed in step V1 to the polyethylene glycol solution for ultrasonic treatment, with an ultrasonic power of 0.3 kW and an ultrasonic time of 20 min, and heat and stir to obtain a quartz fiber suspension at a heating temperature of 50°C and a heating time of 4 h;

[0068] V4: Slowly add the quartz fiber suspension obtained in step V3 to the mixed sand obtained in step V2, the mass ratio of the quartz fiber suspension to the mixed sand is 1.5:4, and slowly stir with a peristaltic pump at a stirring speed of 25 r / min for 2 h, and then dry at a drying temperature of 65°C for 12 h to obtain composite sand;

[0069] V5: Add the binder into the composite sand obtained in step V4 in the form of spraying and stir. The mass ratio of the binder to the composite sand is 4:9. The stirring time is 3 hours. Then, the mixture is dried at a drying temperature of 50°C and a drying time of 24 hours to obtain a main mixture.

[0070] The preparation method of the inner coating material comprises the following steps:

[0071] Y1: Weigh high-purity silica sol, high-purity silicon carbide and high-purity barium silicate in a mass ratio of 3:4:1.5;

[0072] Y2: The high-purity silica sol weighed in step Y1 is subjected to ultrasonic treatment at a power of 0.8 kW and a time of 30 min to obtain a uniform silica sol. The high-purity silicon carbide and high-purity barium silicate weighed in step Y1 are then added to the uniform silica sol and stirred at a speed of 800 r / min for 2 h to obtain an inner coating material.

[0073] Furthermore, the method for preparing the outer base material comprises the following steps:

[0074] X1: Weigh high-purity alumina powder, high-purity silicon carbide powder, high-purity quartz fiber and epoxy resin glue in a mass ratio of 1.5:2:3:3;

[0075] X2: The high-purity aluminum oxide powder and the high-purity silicon carbide powder weighed in step X1 are fully mixed to obtain a mixture I;

[0076] X3: Add the high-purity quartz fiber weighed in step X1 to the epoxy resin glue, heat the temperature to 50°C and stir, the heating time is 60 minutes, the stirring speed is 300 r / min, and the stirring time is 1 hour, to obtain a mixture II;

[0077] X4: Add the mixture I obtained in step X2 to the mixture II obtained in step X3 and stir evenly. The mass ratio of mixture I to mixture II is 2:0.5 to obtain an outer base material.

[0078] This embodiment also provides a method for preparing a composite ultra-high temperature quartz crucible, comprising the following steps:

[0079] Step 1: Weigh 10 parts of the main mixture, 0.5 parts of the inner coating material, and 2 parts of the outer base material;

[0080] Step 2: slowly inject the main mixture weighed in step 1 into the mold of the quartz crucible, and use a hot isostatic press to solidify and shape it at a temperature of 300° C. and a pressure of 100 MPa to obtain a quartz crucible body, and then slowly and evenly inject the outer base material onto the outer surface of the quartz crucible body, and press it at a temperature of 300° C. and a pressure of 200 MPa to obtain a quartz crucible blank;

[0081] Step 3: evenly spraying the inner coating material weighed in step 1 onto the inner surface of the quartz crucible blank obtained in step 2 to obtain a complete quartz crucible precursor;

[0082] Step 4: Place the quartz crucible precursor obtained in step 3 into a high temperature furnace, sinter it at 1500°C in an argon atmosphere with an argon flow rate of 25 L / min for 8 hours, and cool it naturally to room temperature to obtain a composite ultra-high temperature quartz crucible.

[0083] Example 2: A composite ultra-high temperature quartz crucible, characterized in that it is prepared from the following raw materials in parts by weight: 11 parts of a main mixture, 0.5 parts of an inner coating material, and 2.5 parts of an outer base material;

[0084] The preparation method of the binder comprises the following steps:

[0085] S1: Weigh water, polyethylene glycol, sodium polyacrylate and ethylene glycol in a mass ratio of 10:5:0.2:2;

[0086] S2: adding the polyethylene glycol weighed in step S1 into water, heating the temperature to 70°C and stirring for 30 minutes to obtain a polyethylene glycol mixed aqueous solution, then adding sodium polyacrylate to the polyethylene glycol mixed aqueous solution, stirring at room temperature for 7 hours to obtain a viscous mixture;

[0087] S3: Add ethylene glycol to the viscous mixture obtained in step S2 for ultrasonic treatment. The mass ratio of the viscous mixture to ethylene glycol is 2:2. The ultrasonic time is 30 minutes and the ultrasonic power is 0.7 kW. Heat the temperature to 70°C and stir for 2 hours to obtain a binder.

[0088] The preparation method of the condensed quartz sand comprises the following steps:

[0089] M1: Weigh high-purity quartz sand, silane coupling agent and sodium hydroxide solution in a mass ratio of 13:4:1.5;

[0090] M2: The sodium hydroxide solution weighed in step M1, the concentration of which is 1 mol / L, is added to a high-pressure reactor and diluted 5 times with water to obtain a diluted alkaline solution. The high-purity quartz sand weighed in step M1 is added to the diluted alkaline solution and stirred evenly to obtain a mixture solution I, which is then heated to 150° C. for 5 hours, and then naturally cooled to room temperature to obtain hydroxylated quartz sand;

[0091] M3: Add water to the hydroxylated quartz sand obtained in step M2 and filter until the filtrate is neutral to obtain pure hydroxylated quartz sand. Dry the obtained pure hydroxylated quartz sand at a temperature of 60° C. for 24 h, collect the powder, and obtain hydroxylated quartz sand powder;

[0092] M4: Stir and mix the silane coupling agent and water weighed in step M1, the mass ratio of the silane coupling agent to water is 4:15, add 3 mol / L hydrochloric acid, adjust the pH to 4, and obtain a silane coupling agent acid solution, then stir and heat the silane coupling agent acid solution to 80°C and stir for 2 hours to obtain a silanol solution;

[0093] M5: Add the hydroxylated quartz sand obtained in step M2 to the silanol solution obtained in step M4, the mass ratio of hydroxylated quartz sand to silanol solution is 1:3, heat to 70°C and stir for 6 hours, naturally cool to room temperature, centrifuge to remove the solution and dry to obtain condensed quartz sand.

[0094] The preparation method of the composite quartz sand comprises the following steps:

[0095] N1: Weigh condensed quartz sand, high-purity graphite powder and high-purity carbon powder in a mass ratio of 8:2:1;

[0096] N2: The condensed quartz sand, high-purity graphite powder and high-purity carbon powder weighed in step N1 are stirred and mixed evenly, and heated to 1700°C in a resistance furnace under an argon flow rate of 20 L / min for 6 hours, and then naturally cooled to room temperature to obtain composite quartz sand.

[0097] The preparation method of the main mixture comprises the following steps:

[0098] V1: Weigh composite quartz sand, high-purity silicon nitride, high-purity silicon powder, high-purity quartz fiber, polyethylene glycol, binder and ethanol in a mass ratio of 18:7:2:5:5.5:5:4.5;

[0099] V2: Evenly mix the composite quartz sand, high-purity silicon nitride and high-purity silicon powder weighed in step V1 to obtain mixed sand;

[0100] V3: Add the polyethylene glycol weighed in step V1 to ethanol and stir evenly to obtain a polyethylene glycol solution, then add the high-purity quartz fiber weighed in step V1 to the polyethylene glycol solution for ultrasonic treatment, with an ultrasonic power of 0.4 kW and an ultrasonic time of 20 min, and heat and stir to obtain a quartz fiber suspension at a heating temperature of 65°C and a heating time of 4 h;

[0101] V4: Slowly add the quartz fiber suspension obtained in step V3 to the mixed sand obtained in step V2, the mass ratio of the quartz fiber suspension to the mixed sand is 2:4, and slowly stir with a peristaltic pump at a stirring speed of 25 r / min for 2 h, and then dry at a drying temperature of 65°C for 12 h to obtain composite sand;

[0102] V5: Add the binder into the composite sand obtained in step V4 in the form of spraying and stir. The mass ratio of the binder to the composite sand is 5:9. The stirring time is 3 hours. Then, the mixture is dried at a temperature of 60° C. for 24 hours to obtain a main mixture.

[0103] The preparation method of the inner coating material comprises the following steps:

[0104] Y1: Weigh high-purity silica sol, high-purity silicon carbide and high-purity barium silicate in a mass ratio of 3:5:2.5;

[0105] Y2: The high-purity silica sol weighed in step Y1 is subjected to ultrasonic treatment at a power of 1.0 kW and a time of 30 min to obtain a uniform silica sol. The high-purity silicon carbide and high-purity barium silicate weighed in step Y1 are then added to the uniform silica sol and stirred at a speed of 1000 r / min for 3 h to obtain an inner coating material.

[0106] Furthermore, the method for preparing the outer base material comprises the following steps:

[0107] X1: Weigh high-purity alumina powder, high-purity silicon carbide powder, high-purity quartz fiber and epoxy resin glue in a mass ratio of 1.8:3:3:4;

[0108] X2: The high-purity aluminum oxide powder and the high-purity silicon carbide powder weighed in step X1 are fully mixed to obtain a mixture I;

[0109] X3: Add the high-purity quartz fiber weighed in step X1 to the epoxy resin glue, heat the temperature to 60°C and stir, the heating time is 60 minutes, the stirring speed is 400 r / min, and the stirring time is 2 hours, to obtain a mixture II;

[0110] X4: Add the mixture I obtained in step X2 to the mixture II obtained in step X3 and stir evenly, the mass ratio of mixture I to mixture II is 2:1, to obtain an outer base material.

[0111] This embodiment also provides a method for preparing a composite ultra-high temperature quartz crucible, comprising the following steps:

[0112] Step 1: Weigh 11 parts of the main mixture, 0.5 parts of the inner coating material, and 2.5 parts of the outer base material;

[0113] Step 2: slowly inject the main mixture weighed in step 1 into the mold of the quartz crucible, and use a hot isostatic press to solidify and shape it at a temperature of 400° C. and a pressure of 100 MPa to obtain a quartz crucible body, and then slowly and evenly inject the outer base material onto the outer surface of the quartz crucible body, and press it at a temperature of 400° C. and a pressure of 300 MPa to obtain a quartz crucible blank;

[0114] Step 3: evenly spraying the inner coating material weighed in step 1 onto the inner surface of the quartz crucible blank obtained in step 2 to obtain a complete quartz crucible precursor;

[0115] Step 4: Place the quartz crucible precursor obtained in step 3 into a high temperature furnace, sinter it at 1700°C in an argon atmosphere with an argon flow rate of 25 L / min for 8 hours, and cool it naturally to room temperature to obtain a composite ultra-high temperature quartz crucible.

[0116] Example 3: A composite ultra-high temperature quartz crucible, characterized in that it is prepared from the following raw materials in parts by weight: 12 parts of a main mixture, 0.5 parts of an inner coating material, and 3 parts of an outer base material;

[0117] The preparation method of the binder comprises the following steps:

[0118] S1: Weigh water, polyethylene glycol, sodium polyacrylate and ethylene glycol in a mass ratio of 10:6:0.3:3;

[0119] S2: adding the polyethylene glycol weighed in step S1 into water, heating the temperature to 80°C and stirring for 30 minutes to obtain a polyethylene glycol mixed aqueous solution, then adding sodium polyacrylate to the polyethylene glycol mixed aqueous solution, stirring at room temperature for 8 hours to obtain a viscous mixture;

[0120] S3: Add ethylene glycol to the viscous mixture obtained in step S2, the mass ratio of the viscous mixture to ethylene glycol is 2:3, the ultrasonic time is 30 minutes, the ultrasonic power is 0.8 kW, the temperature is heated to 75°C and stirred, the heating time is 2 hours, and a binder is obtained.

[0121] The preparation method of the condensed quartz sand comprises the following steps:

[0122] M1: Weigh high-purity quartz sand, silane coupling agent, and sodium hydroxide solution in a mass ratio of 15:5:1.5;

[0123] M2: The sodium hydroxide solution weighed in step M1, the concentration of which is 1 mol / L, is added to a high-pressure reactor and diluted 5 times with water to obtain a diluted alkaline solution, the high-purity quartz sand weighed in step M1 is added to the diluted alkaline solution and stirred evenly to obtain a mixture solution I, which is then heated to 180° C. for 6 hours, and naturally cooled to room temperature to obtain hydroxylated quartz sand;

[0124] M3: Add water to the hydroxylated quartz sand obtained in step M2 and filter until the filtrate is neutral to obtain pure hydroxylated quartz sand. Dry the obtained pure hydroxylated quartz sand at a temperature of 60° C. for 24 h, collect the powder, and obtain hydroxylated quartz sand powder;

[0125] M4: Stir and mix the silane coupling agent and water weighed in step M1, the mass ratio of the silane coupling agent to water is 5:15, add 3 mol / L hydrochloric acid, adjust the pH to 5, and obtain a silane coupling agent acid solution, then stir and heat the silane coupling agent acid solution to 90° C. and stir for 2 h to obtain a silanol solution;

[0126] M5: Add the hydroxylated quartz sand obtained in step M2 to the silanol solution obtained in step M4, the mass ratio of hydroxylated quartz sand to silanol solution is 1:4, heat to 80°C and stir for 6 hours, naturally cool to room temperature, centrifuge to remove the solution and dry to obtain condensed quartz sand.

[0127] The preparation method of the composite quartz sand comprises the following steps:

[0128] N1: Weigh condensed quartz sand, high-purity graphite powder and high-purity carbon powder in a mass ratio of 10:2.5:1;

[0129] N2: The condensed quartz sand, high-purity graphite powder and high-purity carbon powder weighed in step N1 are stirred and mixed evenly, and heated to 1800° C. for 6 hours in an argon gas flow rate of 20 L / min using a resistance furnace, and then naturally cooled to room temperature to obtain composite quartz sand.

[0130] The preparation method of the main mixture comprises the following steps:

[0131] V1: Weigh composite quartz sand, high-purity silicon nitride, high-purity silicon powder, high-purity quartz fiber, polyethylene glycol, binder and ethanol in a mass ratio of 20:8:2:7:6.5:6:6;

[0132] V2: Evenly mix the composite quartz sand, high-purity silicon nitride and high-purity silicon powder weighed in step V1 to obtain mixed sand;

[0133] V3: Add the polyethylene glycol weighed in step V1 to ethanol and stir evenly to obtain a polyethylene glycol solution, then add the high-purity quartz fiber weighed in step V1 to the polyethylene glycol solution for ultrasonic treatment, with an ultrasonic power of 0.5 kW and an ultrasonic time of 20 min, and heat and stir to obtain a quartz fiber suspension at a heating temperature of 80°C and a heating time of 4 h;

[0134] V4: Slowly add the quartz fiber suspension obtained in step V3 to the mixed sand obtained in step V2, the mass ratio of the quartz fiber suspension to the mixed sand is 2.5:4, and slowly stir with a peristaltic pump at a stirring speed of 25 r / min for 2 h, and then dry at a drying temperature of 65°C for 12 h to obtain composite sand;

[0135] V5: Add the binder weighed in step V1 into the composite sand obtained in step V4 by spraying and stirring. The mass ratio of the binder to the composite sand is 6:9. The stirring time is 3 hours. Then, the mixture is dried at a drying temperature of 70°C and a drying time of 24 hours to obtain a main mixture.

[0136] The preparation method of the inner coating material comprises the following steps:

[0137] Y1: Weigh high-purity silica sol, high-purity silicon carbide and high-purity barium silicate in a mass ratio of 3:6:3.5;

[0138] Y2: The high-purity silica sol weighed in step Y1 is subjected to ultrasonic treatment at a power of 1.2 kW and a time of 30 min to obtain a uniform silica sol. The high-purity silicon carbide and high-purity barium silicate weighed in step Y1 are then added to the uniform silica sol and stirred at a speed of 1200 r / min for 4 h to obtain an inner coating material.

[0139] The method for preparing the outer base material comprises the following steps:

[0140] X1: Weigh high-purity alumina powder, high-purity silicon carbide powder, high-purity quartz fiber and epoxy resin glue in a mass ratio of 2.0:4:3:5;

[0141] X1: Weigh high-purity alumina powder, high-purity silicon carbide powder, high-purity quartz fiber and epoxy resin glue in a mass ratio of 1.8:3:3:4;

[0142] X2: The high-purity aluminum oxide powder and the high-purity silicon carbide powder weighed in step X1 are fully mixed to obtain a mixture I;

[0143] X3: Add the high-purity quartz fiber weighed in step X1 to the epoxy resin glue, heat the temperature to 70°C and stir, the heating time is 60 minutes, the stirring speed is 500 r / min, and the stirring time is 3 hours, to obtain a mixture II;

[0144] X4: Add the mixture I obtained in step X2 to the mixture II obtained in step X3 and stir evenly. The mass ratio of mixture I to mixture II is 2:1.5 to obtain an outer base material.

[0145] This embodiment also provides a method for preparing a composite ultra-high temperature quartz crucible, comprising the following steps:

[0146] Step 1: Weigh 12 parts of the main mixture, 0.5 parts of the inner coating material, and 3 parts of the outer base material;

[0147] Step 2: slowly inject the main mixture weighed in step 1 into the mold of the quartz crucible, and use a hot isostatic press to solidify and shape it at a temperature of 500° C. and a pressure of 100 MPa to obtain a quartz crucible body, and then slowly and evenly inject the outer base material onto the outer surface of the quartz crucible body, and press it at a temperature of 500° C. and a pressure of 400 MPa to obtain a quartz crucible blank;

[0148] Step 3: evenly spraying the inner coating material weighed in step 1 onto the inner surface of the quartz crucible blank obtained in step 2 to obtain a complete quartz crucible precursor;

[0149] Step 4: Place the quartz crucible precursor obtained in step 3 into a high temperature furnace, sinter it at 2000°C in an argon atmosphere with an argon flow rate of 25 L / min for 8 hours, and cool it naturally to room temperature to obtain a composite ultra-high temperature quartz crucible.

[0150] The difference between Comparative Example 1 and Example 2 is that no inner coating material is added, and the rest is the same as Example 2;

[0151] The difference between Comparative Example 2 and Example 2 is that no outer base material is added, and the rest is the same as Example 2;

[0152] The difference between Comparative Example 3 and Example 2 is that no inner coating material and outer base material are added, and the rest is the same as Example 2;

[0153] Obviously, the above comparative examples and embodiments are only a part of comparative examples and embodiments of the present invention, and they and the comparative examples and embodiments based on such references are all within the scope of protection of the present invention.

[0154] The composite ultra-high temperature quartz crucible prepared by the present invention was subjected to relevant tests:

[0155] The composite ultrahigh temperature quartz crucibles prepared in the embodiment and the comparative example were heated to 1400° C., 1500° C., 1600° C. and 1800° C., respectively, and maintained at the above temperature conditions for 150 h, respectively, with a compressed gas flow rate of 75 L / min, and the cracking and corrosion conditions of the prepared composite ultrahigh temperature quartz crucibles were observed.

[0156] Table 1 shows the test results of the prepared composite ultra-high temperature quartz crucible;

[0157]

[0158] The composite ultra-high temperature quartz crucible prepared in Example 1 had cracks of 0.5-1 mm when heated to 1800°C, the surface corrosion took an intermediate value of 145 μm, and the corrosion rate was 0.24 μm / h; for Example 2 and Example 3, no cracking occurred when heated to 1800°C, and the corrosion rate was lower than that of Example 1, indicating that the inner coating material and the outer substrate material had strong corrosion resistance; and further relevant tests were carried out on the comparative example. From the above results, the composite ultra-high temperature quartz crucible prepared in the comparative example all cracked when heated to 1600°C, indicating that the composite ultra-high temperature quartz crucible prepared in the example showed excellent properties in terms of temperature resistance, strength and corrosion resistance.

[0159] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

[0160] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A composite ultra-high temperature quartz crucible, characterized in that: It is prepared from the following raw materials in parts by weight: 10-12 parts of the main mixture, 0.5 parts of the inner coating material, and 2-3 parts of the outer base material; The raw materials for preparing the main mixture include composite quartz sand, high-purity silicon nitride, high-purity silicon powder, high-purity quartz fiber, polyethylene glycol, a binder and ethanol; the raw materials for preparing the composite quartz sand include condensed quartz sand, high-purity graphite powder and high-purity carbon powder; the raw materials for preparing the binder include water, polyethylene glycol, sodium polyacrylate and ethylene glycol; the raw materials for preparing the condensed quartz sand include high-purity quartz sand, a silane coupling agent, a sodium hydroxide solution and hydrochloric acid; The raw materials for preparing the inner coating material include high-purity silica sol, high-purity silicon carbide and high-purity barium silicate; The raw materials for preparing the outer base material include high-purity alumina powder, high-purity silicon carbide powder, high-purity quartz fiber and epoxy resin glue; The preparation method of the condensed quartz sand comprises the following steps: M1: Weigh high-purity quartz sand, silane coupling agent and sodium hydroxide solution in a mass ratio of 10-15:3-5:1.5; M2: The sodium hydroxide solution weighed in step M1 is added to a high-pressure reactor and diluted with water to obtain a diluted alkaline solution, and the high-purity quartz sand weighed in step M1 is added to the diluted alkaline solution and stirred to obtain a mixture solution I, which is then heated and naturally cooled to room temperature to obtain hydroxylated quartz sand; M3: adding water to the hydroxylated quartz sand obtained in step M2 and filtering until the filtrate is neutral to obtain pure hydroxylated quartz sand, drying the obtained pure hydroxylated quartz sand, collecting powder, and obtaining hydroxylated quartz sand powder; M4: Stir and mix the silane coupling agent and water weighed in step M1, wherein the mass ratio of the silane coupling agent to water is 3-5:15, add hydrochloric acid, and control the pH range to 3-5 to obtain a silane coupling agent acid solution, and then heat and stir the silane coupling agent acid solution to obtain a silanol solution; M5: Add the hydroxylated quartz sand obtained in step M2 to the silanol solution obtained in step M4, heat and stir, cool naturally to room temperature, centrifuge to remove the solution and dry to obtain condensed quartz sand.

2. A composite ultra-high temperature quartz crucible according to claim 1, characterized in that: The preparation method of the main mixture comprises the following steps: V1: Weigh composite quartz sand, high-purity silicon nitride, high-purity silicon powder, high-purity quartz fiber, polyethylene glycol, binder and ethanol in a mass ratio of 15-20:6-8:2:3-7:4.5-6.5:4-6:3-6; V2: Evenly mix the composite quartz sand, high-purity silicon nitride and high-purity silicon powder weighed in step V1 to obtain mixed sand; V3: adding the polyethylene glycol weighed in step V1 into ethanol and stirring evenly to obtain a polyethylene glycol solution, then adding the high-purity quartz fiber weighed in step V1 into the polyethylene glycol solution, heating and stirring to obtain a quartz fiber suspension; V4: slowly adding the quartz fiber suspension obtained in step V3 to the mixed sand obtained in step V2, slowly stirring, and then drying to obtain composite sand; V5: The binder weighed in step V1 is added into the composite sand obtained in step V4 by spraying and stirred, and then dried to obtain a main mixture.

3. A composite ultra-high temperature quartz crucible according to claim 2, characterized in that: The preparation method of the composite quartz sand comprises the following steps: N1: Weigh condensed quartz sand, high-purity graphite powder and high-purity carbon powder in a mass ratio of 6-10:1.5-2.5:1; N2: The condensed quartz sand, high-purity graphite powder and high-purity carbon powder weighed in step N1 are stirred and mixed uniformly, heated under an argon atmosphere, and then naturally cooled to room temperature to obtain composite quartz sand.

4. A composite ultra-high temperature quartz crucible according to claim 2, characterized in that: The preparation method of the binder comprises the following steps: S1: Weigh water, polyethylene glycol, sodium polyacrylate and ethylene glycol in a mass ratio of 10:4-6:0.1-0.3:1-3; S2: adding the polyethylene glycol weighed in step S1 into water, heating and stirring to obtain a polyethylene glycol mixed aqueous solution, then adding sodium polyacrylate to the polyethylene glycol mixed aqueous solution, stirring at room temperature to obtain a viscous mixture; S3: Add ethylene glycol to the viscous mixture obtained in step S2, perform ultrasonic treatment, heat and stir to obtain a binder.

5. The composite ultra-high temperature quartz crucible according to claim 1, characterized in that: The preparation method of the inner coating material comprises the following steps: Y1: Weigh high-purity silica sol, high-purity silicon carbide and high-purity barium silicate in a mass ratio of 3:4-6:1.5-3.5; Y2: subjecting the high-purity silica sol weighed in step Y1 to ultrasonic stirring treatment to obtain uniform silica sol, and then adding the high-purity silicon carbide and high-purity barium silicate weighed in step Y1 to the uniform silica sol, stirring to obtain an inner coating material.

6. The composite ultra-high temperature quartz crucible according to claim 5, characterized in that: The ultrasonic power described in step Y2 is 0.8-1.2kw, the ultrasonic time is 30min, the stirring speed is 800-1200r / min, and the stirring time is 2-4h.

7. The composite ultra-high temperature quartz crucible according to claim 1, characterized in that: The method for preparing the outer base material comprises the following steps: X1: Weigh high-purity alumina powder, high-purity silicon carbide powder, high-purity quartz fiber and epoxy resin glue in a mass ratio of 1.5-2:2-4:3:3-5; X2: The high-purity aluminum oxide powder and the high-purity silicon carbide powder weighed in step X1 are fully mixed to obtain a mixture I; X3: adding the high-purity quartz fiber weighed in step X1 to the epoxy resin glue and heating and stirring to obtain a mixture II; X4: Add the mixture I obtained in step X2 to the mixture II obtained in step X3 and stir evenly to obtain an outer base material.

8. The composite ultra-high temperature quartz crucible according to claim 7, characterized in that: The heating temperature in step X3 is 50-70° C., the heating time is 60 min, the stirring speed is 300-500 r / min, the stirring time is 1-3 h, and the mass ratio of mixture I to mixture II in step X4 is 2:0.5-1.

5.

9. A method for preparing a composite ultrahigh temperature quartz crucible according to any one of claims 1 to 8, characterized in that: The steps include: Step 1: 10-12 parts of the main mixture, 0.5 parts of the inner coating material, and 2-3 parts of the outer base material; Step 2: slowly injecting the main mixture weighed in step 1 into the mold of the quartz crucible, curing and molding under heating and pressure conditions to obtain the quartz crucible body, then slowly and evenly injecting the outer base material onto the outer surface of the quartz crucible body, pressing under high temperature and high pressure to obtain the quartz crucible blank; Step 3: evenly spraying the inner coating material weighed in step 1 onto the inner surface of the quartz crucible blank obtained in step 2 to obtain a complete quartz crucible precursor; Step 4: Sintering the quartz crucible precursor obtained in step 3 at 1500-2000° C. in an argon atmosphere, and naturally cooling to room temperature to obtain a composite ultra-high temperature quartz crucible.

Citation Information

Patent Citations

  • Quartz glass crucible and preparation method thereof

    CN102061515A

  • Silicon nitride combined silicon carbide composite barium coating quartz crucible and preparation method thereof

    CN109627047A